MORINGA LEAF SIMPLICIA ENCHANCED HEALTH STATUS AND IMMUNE RESPONSE OF TILAPIA AGAINST Edwardsiella tarda INFECTION - Ratnadilla, Thamara; Wahjuningrum, Dinamella; Widanarni, Widanarni (Indonesian Aquaculture Journal, 2025)
Intensive fish aquaculture increases the risk of diseases like Edwardsiellosis caused by Edwardsiella tarda, which can lead to 30–50% mortality rates. While antibiotics have been used for disease control, excessive use can result in antibiotic residue and bacterial resistance. Moringa leaves (Moringa oleifera) are a promising herbal ingredient containing active compounds like glucomoringin, moringin, flavonoids, tannins, sapponins, alkaloids, and phenols, which can be used in aquaculture. This study aims to evaluate the effect of administering different doses of moringa leaf simplicia (MOLS) through feed for the prevention of E. tarda bacterial infection in tilapia. The research was conducted in two stages, namely in vitro and in vivo testing. The first stage was an in vitro test to determine the dose of moringa leaf extract that can inhibit the growth of E. tarda. The second stage was an in vivo test to evaluate the effect of feeding MOLS on growth performance, health status and immune response, and resistance of tilapia to E. tarda infection. In vivo tests were namely MOLS 12.5 g kg-¹ (M12.5), 25 g kg-¹ (M25), 50 g kg-¹ (M50), positive control (K+) and negative control (K-). The test fish used were tilapia fish measuring 7.77 ± 0.06 g which were kept in 15 aquariums with density of 10 fish per aquarium for 30 days. Fish were challenged on the 31st day with E. tarda cell suspension 106 CFU mL-1 which corresponds of the LD50 value-the bacterial dose that cause 50% mortality in the tested fish population and then the fish were maintained for 7 days. The results showed that increasing the addition of MOLS for 30 resulted in significant improvements (P<0.05) in growth of tilapia with control. The highest abundance of lactic acid bacteria was found in the M12.5 treatment, a significant difference (P<0.05) compared to the control treatment. MOLS also significantly improved the health status and immune response of tilapia (P<0.05), and suppressed the population of E. tarda in kidney and liver organs. Kidney histopathology showed normal to lightly damage in the MOLS treatment observed significantly lower (P<0.05) than the K+ treatment with lightly damage. Liver histopathology also showed normal to lightly damage in MOLS treatment observed significantly lower (P<0.05) than K+ with medium damage. M12.5 treatment showed the highest resistance significantly different (P<0.05) compared to K+ treatment. MOLS was able to improve the health status and immune response, as well as the resistance of tilapia to E. tarda infection with the best dose in feed with the addition of 12.5 g kg-¹ MOLS.